Peramalan Laju Produksi Minyak Bumi Menggunakan Metode Decline Curve Analysis dan ARIMA - Rahma Wati; Sri Wahyuningsih; Syaripuddin Syaripuddin (Jurnal Aplikasi Statistika & Komputasi Statistik, 2019)
The DCA (Decline Curve Analysis) and ARIMA (Autoregressive Integrated Moving Average) methods are quantitative forecasting methods. The assumption of this method is the previous data aspects will continue in the future. DCA calculation is done by determining decline curve type. ARIMA modeling is done by five steps, those are identification model, estimating parameters, testing the parameters significance, diagnostic checking and forecasting. Based on the results of analysis with DCA, obtained that is exponential decline and the results of forecasting showed the decline that tends to be constant. And the analysis using ARIMA, obtained that is the ARIMA model (1,1,0) and the results of forecasting showed relatively constant fluctuations. Keywords: ARIMA, DCA, decline curve, the rate of oil production.